2021
DOI: 10.3390/molecules26072051
|View full text |Cite
|
Sign up to set email alerts
|

Au@Pt Core-Shell Nanoparticle Bioconjugates for the Therapy of HER2+ Breast Cancer and Hepatocellular Carcinoma. Model Studies on the Applicability of 193mPt and 195mPt Radionuclides in Auger Electron Therapy

Abstract: 193mPt and 195mPt radionuclides are therapeutically attractive Auger electron emitters with notably high Auger electron yield per decay. The present paper summarizes the first step of research on the applications of core-shell (Au@Pt) nanoparticles for electron Auger therapy of HER2+ (human epidermal growth factor receptor 2) breast cancer and hepatocellular carcinoma. Gold nanoparticles (30 nm) were synthesized covered with a platinum shell at high efficiency (>80%) and were further evaluated for in vitro … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 35 publications
6
13
0
Order By: Relevance
“…These results demonstrated that DOX–PEG–AuNPs–PEG–([ 131 I]Tmab) bioconjugate binds specifically to HER2 receptors expressed on SKOV-3 cells with high affinity. Our findings were in good agreement with other publications, where various NPs conjugated with Tmab were studied for receptor-binding properties [ 19 , 20 , 21 ].…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…These results demonstrated that DOX–PEG–AuNPs–PEG–([ 131 I]Tmab) bioconjugate binds specifically to HER2 receptors expressed on SKOV-3 cells with high affinity. Our findings were in good agreement with other publications, where various NPs conjugated with Tmab were studied for receptor-binding properties [ 19 , 20 , 21 ].…”
Section: Resultssupporting
confidence: 93%
“…This was due to the detected radioactivities being close to the background which confirmed the lack of specific binding to MDA-MB-231 cells. Similar results were obtained by Wawrowicz et al [ 19 ], where receptor affinity for Au@Pt-PEG–[ 131 I]Tmab was studied.…”
Section: Resultssupporting
confidence: 88%
“…Since we observed a marked, time-dependent increase in ROS production, we asked whether redox stress triggered by Au@Pt and PtNPs refers to the particle-dependent, apoptotic changes in HCC. The typical, molecular hallmarks of apoptosis, such as chromatin condensation and apoptotic body formation, have been previously confirmed with confocal imaging of HCCs after treatment with Au@Pt [ 31 ]. To extend that research, here, we employed Annexin-V assay.…”
Section: Resultsmentioning
confidence: 81%
“…The following supporting information can be downloaded at: . References [ 31 , 38 , 39 , 40 , 41 ] are cited in Supplementary Materials.…”
mentioning
confidence: 99%
“…Anticancer drug delivery systems represent a widely investigated research area in the context of nanoparticles medical application. The surface of nanoparticles can be modified with proper vectors (such as antibodies, peptides, or small biologically active molecules) which have high affinity to the receptors on tumor cells, and the number of these targeting ligands bound to one nanoparticle can be much more than one [16]. Specific binding to transmembrane receptors improves the delivery of radioactivity to the targeted tissue, which leads to improved therapeutic efficacy.…”
Section: Introductionmentioning
confidence: 99%